Field report PAC 671: Najib Wahab & Associates, Appvolusi Sdn. Bhd / Azrul Aizat Norazame - Norazame, Azrul Aizat (Universiti Teknologi MARA, Terengganu, 2024)
NWA Corporate House and Najib Wahab & Associates are the company's main revenue sources. These companies provide critical services required for the smooth running and compliance of organisations. NWA Corporate House provides complete company secretarial services to help businesses comply with legal frameworks such as the Companies Act 2016, the Income Tax Act 1967, and the Sales and Services Act 2018. This compliance is crucial for businesses to avoid legal issues and run smoothly in the market.